Application of carbon-based quantum dots in photodynamic therapy. (25th January 2023) - Karagianni, Alexandra; Tsierkezos, Nikos G.; Prato, Maurizio; Terrones, Mauricio; Kordatos, Konstantinos V.
Abstract: Photodynamic Therapy (PDT) is a non-invasive therapeutic modality that can treat a wide variety of cancer types by means of photosensitizer drug, light, and oxygen. Due to enhanced specificity and fewer side effects, PDT can be an alternative approach for cancer treatments. However, conventional photosensitizers (PSs) exhibit low selectivity, hydrophobicity, and limited photophysical properties. Nanotechnology emerges as a potential solution to these issues and improves PDT efficiency. Nanomaterials such as Carbon Quantum Dots (CQDs) and Graphene Quantum Dots (GrQDs) have been widely applied on PDT research recently, regarding their excellent photoluminescence properties, biocompatibility, as well as their hydrophilicity. The present review article summarizes the main features of PDT and carbon-based quantum dots with an emphasis on used PSs and methods for synthesis of carbon dots. Additionally, the most recent applications of CQDs and GrQDs in PDT have been extensively discussed. The main conclusion that arises is that carbon-based quantum dots seem to be a powerful tool in cancer diagnosis and treatment. Graphical abstract: Image 1